FLYPAPER EFFECT TERHADAP BELANJA DAERAH PADA KABUPATEN BIREUEN - Imam Malik; Lakharis Inuzula (Program Studi Administrasi Bisnis, 2021)
The purpose of this study is to analyze the effect of PAD and DAU on Regional Expenditures and then analyze the flypaper effect. The sampling technique used is purposive sampling with a sample of the Realization Report of the Regional Revenue and Expenditure Budget of Bireuen Regency in 2011-2015. The data used in this research is secondary data. The analytical method used is descriptive statistical test, hypothesis testing and multiple linear regression models. The result of this study is that DAU and PAD simultaneously have a significant effect on Regional Expenditures. Partially, DAU has no significant effect on Regional Expenditures and PAD has a significant effect on Regional Expenditures. During the research period, there was a flypaper effect in Bireuen Regency because the value of DAU to Regional Expenditures was greater than the value of PAD to Regional Expenditures.